Development of economic, political and ecological values in entrepreneurs. Study focused on filmmakers - Lozano Treviño, David Fernando; Abreu Quintero, José Luis; Almaguer Rocha, Alberto; Cabral Aviña, Cristóbal Eduardo (Spenta University Mexico, 2016)
This research defines the essence of filmmakers as entrepreneurs and how they express their different values in their films. The types of values are defined aligned to film entrepreneurs. How film producers develop their economic values and how they benefit their Film Production Organizations and countries arise. How film entrepreneurs increase their political values within their companies and how power and leadership are key concepts in such virtues are analyzed. Finally, the importance of ecological values and how they are promoted by film business men and women in search of environmental sustainability is highlighted.